(untitled) (Architecture Image Studies, 2026)
The article presents a critical analysis of Fernand Pouillon’s hotel work in southern Algeria, considered as a pioneering experience of contextualized modernity. It explores how the architectural, constructive, morphological, and climatic logics of Saharan vernacular are reinterpreted in a modern language, expressing a post-colonial national identity. Beyond esthetics, the study analyzes how Pouillon translates operational principles of the vernacular -compactness, thermal inertia, introversion, continuity with the site, and mineral materiality- into an architecture adapted to contemporary demands of thermal comfort, passive cooling with energy efficiency, sustainable tourism, and institutional representation. In the context of building a modern national identity after 1962, the development of an Algerian Saharan tourism was accompanied by the construction of hotel infrastructures. However, starting from the 1970s, these projects tended to align with standardized international models, often unsuitable for the local climate and dependent on mechanical air conditioning. Pouillon’s approach stands out distinctly from this evolution by proposing an architecture rooted in the logics of the site and the climate. The Saharan hotels he designs are situated at the intersection of colonial legacies, modernist influences, and vernacular references, contributing to shaping the tourist image of the Algerian Sahara after independence. The comparative analysis of three emblematic hotels -El-Gourara, M’Zab, and El Djanoub- highlights common principles: topographical integration, use of local materials, organization around patios (courtyards), and creation of adapted thermal atmospheres. The methodology is based on a cross-sectional approach combining morpho-stylistic analysis and qualitative evaluation of bioclimatic systems. The results show that Pouillon’s architecture is neither an imitation nor a pastiche, but a reinterpretation of the fundamental logics of the vernacular. It embodies a functional Saharan regionalism, where cultural and environmental dimensions are inseparable, in contrast to later productions often reduced to mere decoration. Ultimately, the article highlights the relevance of this approach in the context of an energy and climate crisis. Pouillon’s achievements appear as relevant references for rethinking architecture in desert environments, prioritizing passive and contextualized solutions rather than energy-intensive technical devices.